Default sequence of Mozart’s compositions during pregnancy gave higher dendritic density in the cerebrum and cerebellum of Rattus norvegicus offsprings compared with reversed sequence and control - Harry Mangasi Binsar Panjaitan; Hermanto Tri Joewono; Widjiati Widjiati (Universitas Airlangga, 2019)
Objectives: This study aim to determine sequence of Mozart songs in the analyzing differences in dendritic density of cerebellum and cerebellum of new born Rattus novergicusMaterials and Methods: Experimental study randomized post test only control group design using Rattus norvegicus. Animal subjects were divided into three groups which were control group, and the treatment group that were given exposure to default sequence and reversed sequence of Mozart's music from gestation day 10. We used a comparison test in the analysis expression of BDNF.Results: In the cerebrum there was a significant difference in the Mozart group in reverse rather than with Mozart standard sequence and in standard Mozart group with no exposure group, with p=0.003 and p=0.000. In the cerebellum there was a significant difference in the group in reverse rather than with standard Mozart and in the standard Mozart group with the control group, with p=0.000 and p=0.000. However, there was no significant difference between control group and Mozart group upside down in cerebrum and cerebellum with p=0.109 and p=0.077Conclusion: The density of dendrites in the cerebrum and cerebellum of Rattus norvegicus newborn exposed to Mozart's music during pregnancy with standard Mozart sequence was higher than that in those receiving reverse order and without exposure. There were no significant differences between the density of the cerebrum and cerebellum dendrites between groups exposed to reversed sequence of Mozart composition and those without exposure.